Gait aid use for people with and without dementia: A comparison of practice between health and non‐health professionals among Australian community care staff. (6th October 2021) - Lee, Den‐Ching A.; Burton, Elissa; Meyer, Claudia; Hunter, Susan W.; Suttanon, Plaiwan; Hill, Keith D.
Abstract: Gait aid provision is a standard approach to improve mobility and balance for older people. This research aims to understand and compare community care staff practice (health vs. non‐health professionals) for gait aid use by people with and without dementia. A cross‐sectional survey was conducted with Australian community care staff between October 2020 and February 2021. Survey items consisted of closed/open‐ended questions to explore staff practice for people with/without dementia, and assessments/procedures health professionals used for people with dementia. Likert‐scale items gauged staff agreement on factors that influenced their decisions regarding gait aid use for people with dementia. Univariate logistic regression analyses were used to examine staff practice for people with/without dementia and their interaction effects, and factors that influenced decision‐making regarding gait aid use for people with dementia. Content analyses were used to collate responses on assessments/procedures used for people with dementia. Health ( n  = 109) and non‐health professionals ( n  = 138) completed the survey. Compared with non‐health professionals, health professionals were more likely to (1) refer the person without dementia [odds ratio, 95% CI: 23.9 (12.1, 47.3), p  < .01] and person with dementia [27.8 (12.5, 61.7), p  < .01] to a physiotherapist for gait aid assessment, (2) agree with gait aid use if the person with dementia: (a) lives with someone who can monitor gait aid safety [coefficient, 95% CI: −0.75 (−1.29, −0.21), p  = .01], (b) performs well on a cognitive functional screen [−0.68 (−1.20, −0.16), p  = .01] and (c) gives feedback about gait aid use [−0.64 (−1.15, −0.12), p  = .02]. No interaction effects existed between health/non‐health professionals and whether the person had dementia/no dementia on the practice options examined. Health professionals infrequently reported using single/dual task, simple/complex gait or motor sequence testing to assess people with dementia for gait aid use. Strategies such as developing decision aid tool(s) may guide mobility practice for community care staff.